Efektivitas Dalam Meningkatkan Kinerja Karyawan Pada Best Western Kindai Hotel Banjarmasin - Ikhsan Rafi Hidayat; Saladin Ghalib; Fitriyadi Fitriyadi; Hairudinor Hairudinor (Lambung Mangkurat University, 2021)
This study aims to see whether the training provided by the Best Western Kindai Hotel Banjarmasin has been effective or not. In the process, this study uses qualitative methods where the results show that the training provided by the Best Western Kindai Hotel Banjarmasin to its employees has shown effective results in its implementation. .Basically, the company always wants every training that is carried out to be effective and produce effective output as well. In its efforts, the Best Western Kindai Hotel Banjarmasin always strives for how every training given is always effective and produces effective outputs too, by bringing in trainers who are competent in their fields with the hope of meeting the factors of effectiveness itself, such as Trainer Clarity, Training Place, Communication Trainers and Training Materials so as to achieve effective training and achieve the vision and mission of the company. Keywords : Training, Effectiveness, Trainer, Trainer Clarity, Training Place, TrainerCommunication, and Training Materials.